2016
DOI: 10.1177/1753465816663978
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled asthma and its risk factors in adult Chinese asthma patients

Abstract: Background:Asthma affects a large number of patients in China, but relatively little is known about asthma management among Chinese patients. This study aims to estimate asthma control rate among adult Chinese patients and to identify predictors associated with uncontrolled asthma.Methods:A total of 4125 asthma patients aged ⩾17 years and representing all regions of mainland China except Tibet were surveyed. Asthma control status was assessed using the Asthma Control Test (ACT) and classified as controlled (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 27 publications
5
27
0
3
Order By: Relevance
“…In the present study, the median treatment adherence rate reported by portable home nebulizer devices was 69.9%, which compares favourably to many previous reports among children in other regions worldwide: the median electronically monitored adherence was 58.4% and 46%, respectively, in two studies in the USA [6,12,13], changing from 54% and 41% at Month 4 to 47% and 31.5% at Month 12 in patients with controlled and uncontrolled asthma, respectively, in a study from Brazil [14], and 49.5% in a study from The Netherlands [15]. Results of the present study also compared favourably to other studies in China investigating treatment adherence in patients with asthma (adults or children) [16][17][18]. Furthermore, the World Health Organization reported that mean adherence was approximately 50% based on key studies in adults and children [19].…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, the median treatment adherence rate reported by portable home nebulizer devices was 69.9%, which compares favourably to many previous reports among children in other regions worldwide: the median electronically monitored adherence was 58.4% and 46%, respectively, in two studies in the USA [6,12,13], changing from 54% and 41% at Month 4 to 47% and 31.5% at Month 12 in patients with controlled and uncontrolled asthma, respectively, in a study from Brazil [14], and 49.5% in a study from The Netherlands [15]. Results of the present study also compared favourably to other studies in China investigating treatment adherence in patients with asthma (adults or children) [16][17][18]. Furthermore, the World Health Organization reported that mean adherence was approximately 50% based on key studies in adults and children [19].…”
Section: Discussionsupporting
confidence: 65%
“…In this study, asthmatic patients whose age was 35 or above were nearly three times more likely to have uncontrolled asthma when compared with those whose age was between 18 and 34. This nding is supported by studies done in Spain (32), China (33), and Saudi Arabia (15). Similarly, a study done in Jimma, Ethiopia, also stated that the probability of getting well-controlled asthma was more than three times higher in the age group of 14-34 years than older age groups (21).…”
Section: Discussionmentioning
confidence: 66%
“…Oshikoya et al demonstrated that alternative medicine used by 25% of asthmatics, 8 Dalcin et al reported that 48.5% were not using inhaler properly. 7 Non-compliance about medication is another factor present in about 50% in asthmatics by. 9 Recent international guidelines define asthma control in terms of two domains: impairment and risk.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that 48.5% were not using inhaler properly with 12.6% using oral medication (oral xanthenes steroids) instead of inhaler therapy which is corner stone of current asthma treatment. 7 Non-compliance about medication is another factor present in about 50% in asthmatics. 9 Psychological fears about medication side effects are also prevalent in about 14.2%, thus compromising regular medication use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation